Legal measures of a cassational appeal against decisions of the court of first instance and decisions of the court of appeal in administrative proceedings - Samara , Vitalii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
Relevance. The legal dimension of cassational appeal in Ukrainian administrative proceedings requires comprehensive analysis in the context of ongoing judicial reforms and European integration. Contemporary challenges include the need for effective judicial control mechanisms, uniform application of legal norms, and implementation of "cassational filters" that impact access to justice. Recent amendments to procedural legislation and evolving judicial practice necessitate examination of cassational procedures to ensure compliance with European standards of justice.Research objective. This study aims to analyze the legal dimension of cassational appeal procedures for first instance and appellate court decisions in Ukrainian administrative proceedings. The research evaluates the role of cassational courts in ensuring justice and legality while examining fundamental principles including the rule of law, legal certainty, and access to justice. The study identifies existing gaps in legislation and judicial practice, proposing solutions for enhancing cassational control mechanisms.Research methodology. The research employs a multidisciplinary methodological approach combining comparative legal analysis, systematic analysis of current legislation, and examination of judicial practice. The study utilizes formal-logical methods for analyzing legal concepts and institutions, comparative methodology for evaluating international experience in cassational proceedings, and empirical analysis of court decisions to identify practical challenges and trends. The research also incorporates elements of sociological and statistical analysis to assess the effectiveness of cassational procedures and their impact on access to justice.Research results. The study reveals significant challenges in the current system of cassational appeals in administrative proceedings, including limitations in cassational court powers, procedural inefficiencies, prolonged case review periods, and unequal access to justice. The analysis demonstrates that the implementation of cassational filters in minor cases, while intended to reduce judicial workload, has created additional barriers to effective legal protection. The research identifies key areas requiring legislative and procedural improvements, including enhanced clarity in cassational grounds, streamlined procedures for case admission, and better integration of European standards of judicial review. The findings contribute to the development of recommendations for reforming administrative court proceedings and improving the overall effectiveness of judicial control mechanisms in Ukraine.